Les ouvriers au cinéma - Matéo Alaluf (Images du Travail, Travail des Images)
The first film in the history (of cinema), La sortie de l’usine Lumière (1895), is also the first film about work. Since then, through fiction, documentary or direct cinema, work, the workmen and their class have given rhythm to all the history of cinema. Unlike the traditional representation of work by the skilled, male, worker of the big industry, cinema put diversified workers and activities on stage. The project to "reproduce" by the image the real world was really shaped by the representation of the workmen in cinema. The question was not, by this attempt, to illustrate work by images, nor to think work starting from the images, but was an attempt to think it with images to create new images and thoughts. Then this cinema could open the possibility of a specific language able to widen our intelligence of the world.